Social Abandonment-Forgetfulness and Institutionalized Confinement as Slow Juvenicide (Andamios, Revista de Investigación Social, 2025)
The penitentiary confinement has been consolidated as a power device, key to the functioning of the contemporary world and its political project. The accent placed on punitive punishment, faded the institutional objective of the administration of justice; placing at a disadvantage the most precarious sectors: the youth in this case. The triad composed by the institutionalization of confinement, the necropolitics and the maquilas of crime, gave way to an immediate annihilation, legible from juvenicide, and to social abandonment-forgetfulness, as lethargic annihilation. This article, with a qualitative approach, proposes to critically analyze the relationship between juvenicide - abandonment-social forgetfulness in the prison context, based on narrative interviews implemented with young people deprived of their liberty between 2017 and 2021.
Keywords: Abandonment-social forgetfulness; confinement; maquilas of crime; juvenicide; social violence